KONSEPTUALISASI METAFORA DARI PENGALAMAN EMOSI: STUDI KASUS PADA MAHASISWA UNIVERISTAS INDONESIA - Gagar Asmara Sofa (PRASASTI: Journal of Linguistics, 2019)
In a metaphorical expression can contain a concept that describes a person's emotional experience (Kövecses, 2000). The following study aim to find the conceptualization of emotional metaphors—happy, sad, fear, angry, and love—on students of Univesitas Indonesia. Sixteen respondents, seven males and nine females, participated in this research. Respondent’s data collected using self-report in a qualitative form. Research result appear to support statement and previous studies which explains that metaphors apply not only as linguistic feature but also giving concrete picture in abstract or conceptual matters. Besides theoretical benefits, researcher also aim to add more contextual studies, specifically in bahasa Indonesia, regarding the relationship between emotion-related conceptual metaphors through the production of metaphors relating to emotional experience. This study has limitations  regarding the lack of depths in studies about culture, considering previous studies by Yu (1995) and Nguyen (2013) highlighted that cultural differences influence the various production of emotional-conceptual metaphors. Future research can incorporate interview and experiment to ignite the emotion-related metaphors.